Association of genitourinary infections and cervical length with preterm childbirth - Bernardo,F.M.M. (2021)
A prospective cohort study was conducted on a convenience sample of 1370 pregnant women with a gestational age of 20 to 25 weeks in the city of Ribeirão Preto. Data on obstetrical history, maternal age, parity, smoking habit, and a history of preterm delivery was collected with the application of a sociodemographic questionnaire. Cervical length was determined by endovaginal ultrasound, and urine and vaginal content samples were obtained to determine urinary tract infection (UTI) and bacterial vaginosis (BV), respectively. The aim of this study was to verify the association of cervical length and genitourinary infections with preterm birth (PTB). Ultrasound showed no association of UTI or BV with short cervical length. PTB rate was 9.63%. Among the women with PTB, 15 showed UTI (RR: 1.55, 95%CI: 0.93–2.58), 19 had BV (RR: 1.22, 95%CI: 0.77–1.94), and one had both UTI and BV (RR: 0.85, 95%CI: 0.13–5.62). Nineteen (14.4%) PTB occurred in women with a cervical length ≤2.5 cm (RR: 2.89, 95%CI: 1.89–4.43). Among the 75 patients with PTB stratified as spontaneous, 10 showed UTI (RR: 2.02, 95%CI: 1.05–3.86) and 14 had a diagnosis of BV (RR: 1.72, 95%CI: 0.97–3.04). A short cervical length between 20 and 25 weeks of pregnancy was associated with PTB, whereas UTI and BV determined at this age were not associated with short cervical length or with PTB, although UTI, even if asymptomatic, was related to spontaneous PTB.